Tinjauan Yuridis tentang Rechtvinding (Pemenuhan Hukum) dalam Hukum Perdata Indonesia - K Martam, Nurmin (Universitas Gorontalo, 2018)
The law has a function to provide protection to human interests (all human beings without exception). Therefore, the law must be implemented so that human interest can be protected. In practice, the law may proceed normally and peacefully, but there may also be legal violations in practice. In this case the law that has been violated must be enforced. It is through law enforcement that this law becomes a reality. In upholding the law there are three elements that must always be considered: legal certainty (Rechtssicherheit), usefulness (Zweckmassigkeit) and justice (Gerechtigkeit).In the life of society required a legal system to create a harmonious and orderly society life. In fact the law or legislation that is made does not cover all cases that arise in society, making it difficult for law enforcement to complete the case. In the scope of positive law in Indonesia, the principle